PENGEMBANGAN MODEL INSTRUMEN PENILAIAN KINERJA GURU TK - Ridlo, Saiful; Supriyanto, Supriyanto (Jurnal Penelitian Pendidikan, 2012)
The academic purpose of kindergarten differs from any other academic puposes of schools. This fact implies differences in both learning process and evaluation. In kindergarten, the learning is thematic, and the evaluation is meant to know the students’ development. In schools, learning in each subject of study is independent, and the evaluation is to know how far the competence each student reaches. In addition, the difference causes to task of kindergarten teacher. So to evaluate kindergarten teacher needs special instrument of teacher’s performance appraisal which differs from any instruments related to teacher appraisals. This research is to formulate kindergarten teacher performance appraisal instrument (KTPAI). This research takes place in Surakarta which involve supervisor, headmaster, and teacher of kindergarten. Data evaluation of factual KTPAI and need asessment of KTPAI are compiled by supervisor and headmaster of kindergarten. The result of this research insists to develop factual KTPAI. Developed KTPAI is differences from factual KTPAI. The differences are: (a) comprehensive competence appraised, (b) distinctness in appraisal procedur and describer of each indicator, (c) compability of instrument with the kindergarten teacher’s task , (d) cohesiveness dan transparency in result of appraisal, and (e) certainty of appraisal result status, and follow up planning.